Analisis Yuridis Delik Perjudian Dalam Pasal 303 KUHP dan Implikasinya Terhadap Penegakan Hukum di Indonesia (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Enforcing Article 303 of the Indonesian Criminal Code (KUHP), which criminalizes unauthorized gambling activities, presents numerous challenges for law enforcement agencies. Despite strict penalties including imprisonment and fines, proving the elements of the offense—such as offering gambling opportunities, operating without permission, and the intent of the offender—remains difficult. Gambling activities are often conducted covertly, complicating evidence collection and witness testimony. Resource constraints, including limited personnel and technological support, further hinder effective enforcement. Corruption and interference within law enforcement also undermine efforts to combat illegal gambling. Additionally, the emergence of online gambling creates legal gaps as Article 303 KUHP predates the digital era, requiring supplementary regulations like the Electronic Information and Transactions Law (UU ITE). Social and cultural attitudes that tolerate gambling as entertainment or income exacerbate enforcement difficulties. Poor inter-agency coordination results in inconsistent prosecution and weak deterrence. Upholding legal principles such as legality, evidence, and fairness is essential to prevent abuse of power and ensure justice. Overall, addressing these multifaceted obstacles requires enhanced resources, better legal frameworks, stronger institutional collaboration, and public education.